Strategie międzynarodowych przedsiębiorstw w Polsce - wyniki badań - Zając, Czesław (Strategies of international companies in Poland - research results, 2006)
Business strategies of companies acquired by international corporations are often changed by them. New owners either continue or imitate these strategies. The results of the research carried out by the author in ten big companies located in Wroclaw and Jelenia Gora where processes of mergers and acquisitions took place indicate that international companies completely changed strategies of acquired companies. This fact also reflects the process of internationalization of business activity of these global corporations. New owners restricted business authonomy of acquired companies as well. They protect only their core business and in fact they transform these companies into production units.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1137, s. 322-331